Every Context has a Context - Barnhart, J. E. (Scottish journal of theology, 1980)
Definition.—I define Epistemological Primitivism as the view that a given text exists in a state of nature or a condition of primordial meaning. It is the literary equivalent to the version of empiricism which stresses the passivity of the mind and the purity of the data in the knowing process. The impossibility of holding consistently to epistemological primitivism is seen when (1) the interpreter recognises that a text gains cognitive meaning only if it is interwoven with other texts and (2) the interpreter actively brings to the text a selective factor by designating which texts will interlace more predominantly and directly with one another.Example.—The famous or infamous passage of Romans 9.11–24 serves as a vivid example of a network of interwoven texts whose overall impact forces the conclusion that Paul is advancing a doctrine of strict predestination. In this passage, each verse seems to prepare the way for the following verse in elaborating the theme of predestination of human choice itself. In his book The Debate About the Bible evangelical Christian Stephen Davis, recognizing the force of the Romans 9 passage, writes, ‘I do not claim to know how to reconcile Paul's teachings on election with the Bible's apparent commitment to the notion that people are free and morally responsible agents.’ Davis' point is that within the Bible are texts other than Romans 9 which seem to force the conclusion that some human choices are neither caused by God nor predestined.